The Impact of Education and Training on the Labour Market Experiences of Young Adults - Kevin Denny; Colm Harmon (Institute for Fiscal Studies (IFS), 2000)
This paper uses pooled cross-section data on recent school leavers in Ireland to model the determinants of labour market status and wages for young adults. Firstly we use a multinomial logit model to analyze whether individuals exit school to employment, unemployment or higher education. Family background is an important predictor for participation in higher education reflecting the degree of rationing in the system. The level of educational attainment influences the probability of entering higher education or employment. The estimates for earnings functions show large differences across gender with males being rewarded significantly higher. The returns to training are positive though biased upwards by sample selection particularly for females.
Keywords: J31; J64; 330; youth; earnings; education; Bildungsertrag; Junge Arbeitskräfte; Irland